Different and unified responses of soil bacterial and fungal community composition and predicted functional potential to 3 years’ drought stress in a semiarid alpine grassland - Wan, Qian; Li, Lei; Liu, Bo; Zhang, Zhihao; Liu, Yalan; Xie, Mingyu (Frontiers in Microbiology, 2023)
Soil microbial communities are key to functional processes in terrestrial ecosystems, and they serve as an important indicator of grasslands status. However, the responses of soil microbial communities and functional potential to drought stress in semiarid alpine grasslands remain unclear. Here, a field experiment was conducted under ambient precipitation as a control, −20% and −40% of precipitation to explore the responses of soil microbial diversity, community composition and predicted functional potential to drought stress in a semiarid alpine grassland located in the northwest of China. Moreover, 16S rRNA gene and ITS sequencing were used to detect bacterial and fungal communities, and the PICRUST and FUNGuild databases were used to predict bacterial and fungal functional groups. Results showed drought stress substantially changes the community diversity of bacteria and fungi, amongst which the bacteria community is more sensitive to drought stress than fungi, indicating the diversity or structure of soil bacteria community could serve as an indicator of alpine grasslands status. However, the fungal community still has difficulty maintaining resistance under excessive drought stress. Our paper also highlighted that soil moisture content, plant diversity (Shannon Wiener, Pieiou and Simpson) and soil organic matter are the main drivers affecting soil bacterial and fungal community composition and predicted functional potential. Notably, the soil microbial functional potential could be predictable through taxonomic community profiles. Our research provides insight for exploring the mechanisms of microbial community composition and functional response to climate change (longer drought) in a semiarid alpine grassland.